The history of Samos to 439 B. C. - Barron, J; J. P. Barron (1961)
The aim of this thesis is to establish the political, economic, and military history of Samos over a millennium, from the first arrival of colonists in the Minoan and Mykenaian Ages to the submission of Samos to imperial Athens in 439 B.C. There is little evidence available for the earlier part of this period. And such later traditions about the Ionian Migration as there are have come under severe attack by modern writers, both in detail and on general grounds of chronology. But there are striking instances of the accurate preservation of information going back at least as far, notably in the case of Mopsos of Kolophon, now confirmed even as to date by Hittite records and by the bilingual inscription of Karatepe. Consequently, it is reasonable to take the traditional narrative as a basis, and see whether it receives confirmation from other sources, chiefly archaeological. Apart from the autochthonous Lelegian king Ankaios, we read in ancient writers of several different immigrant groups in the island: fugitives from Krete in the time of Minos, on their way to found Miletos; 'Aiolians' from Lesbos, sent to found a cleruchy some time before the Trojan War; 'Karians' under Tembrion; 'Ionians' from Epidauros under the leadership of Prokles. Prokles' son Leogoros became involved in war against Androklos, founder of Ephesos and one of the Neleid leaders of the general Ionian Migration. This fact enables us to fix the traditional date of Prokles' arrival in Samos to c. 1125, since the Migration took place four generations after the Sack of Troy, which should be dated, following Herodotos and with archaeological confirmation, to c. 1240. The archaeological remains in Samos agree with these traditions. At Tigani there is Minoan pottery contemporary with - or even slightly earlier than - that from the settlements at Miletos. Gradually this gave way to Mykenaian styles, until the Kretan element had quite disappeared. By the time of the Trojan War, however, the Greek element had left Tigani, no doubt replaced by Tembrion's 'Karians'. When the next Greek pottery appears it is LH III C and Sub-mykenaian, not at Tigani but at the Heraion. It may be, therefore, that of the two settlements under Tembrion and Prokles mentioned by the Etymologicon Magnum Tigani is Astypalaia, the Heraion Chesia. In the course of the Ionian Migration, the new Samians sided with the natives against the Neleids, and for a while the island was conquered and held by Androklos. The Samians went into exile for ten years, some traditionally to Anaia and others to Samothrake. There is evidence that a third group sailed further, and founded Kelenderis in Kilikia: the name of this Samian colony occurs in the Karatepe inscription, invoking Ba'al KRNTRS; and since Samian interest in the orient was not resumed until half a century after that inscription was set up, the Greek place-name would seem to have been given before the Dark Age. Names in -nd- of course are as commonly Anatolian as Greek. But there is only one other Kelenderis, and that near Epidauros, serving to confirm that the Samians did indeed come from the eastern Argolid. There is other evidence in support of this tradition (which can be traced as far back as Herodotos in an explicit form), notably the fact that the eponymous hero of the Samian colony Perinthos (602 B.C.) was an Epidaurian and companion of Orestes. For more than three hundred years, c. 1100-750, we are virtually without evidence for Samian history. We must infer from the names of tribes and months that the traditions of Neleid Ionia were assimilated during this period, and it is probable that Samos received Neleid kings. Otherwise there is only the small but steady sequence of pottery and primitive architecture at the Heraion to assure us of the continuity of the islands's habitation. Recorded history reopens in the second half of the eighth century, when we find the self-conscious Ionians destroying the Karian-infiltrated town of Melie. It seems that Samos and Priene made the attach, against the vain resistance of Miletos, itself part Karian, and Kolophon, Melie's metropolis. The victors parcelled out the territory between them, Priens taking Melie itself, Samos the coastal strip northwards from there to Ephesos. The precise border of the two parcels was to be a matter of recurrent dispute between Samos and Priene. It was about the same time that these Ionian alliances were swept into the wider struggle which grew from the agrarian dispute of Chalkis and Eretria over Lelanton. Samos fought on the side of Chalkis, and at the same time helped Sparta against Messenia and received help from Corinth, while Miletos sent aid to Eretria and may have opposed Sparta on behalf of Messenia. The literary tradition of the alliances has archaeological support. Samos shared in the Athenian disaster at Aigina c. 700, and, like Athens, spent much of the first half of the seventh century in reconstruction. This century was politically and economically the age of the Geomoroi, certain defined artistocratic families said to have held their lands ever since the original settlement. Their period of rule marked the avoidance of warfare in favour of commercial expansion overseas. In the first half of the century they had inaugurated large-scale trade with the Near-Eastern kingdoms and with Kypros. In the second half they were the first to find a new source of silver and tin at Tartessos, Cadiz (638 B.C.). Some time previously Samians had become active in Egypt: first mercenaries in the service of Psamatik I; later, after the establishment of Milesian Naukratis c. 650, merchants who secured a special place in the treaty-port. After a short interlude of tyranny, the Geomoroi founded a group of colonies in Propontis, of which the most notable was Perinthos (602. B.C.). Ensuing warfare with Megara, Lesbos, and Priene, weakened the oligarchy and led to the rise of a short-lived democracy, followed by tyranny under Syloson I c. 590. Five years later he was able to make an alliance with Miletos, now entering two generations of stasis and glad even of so unlikely an ally as Samos. Priene was defeated at last, and a new division made of the lands of the Mykale peninsula. Syloson was succeeded by a relative, perhaps a nephew, Polykrates I, whose existence, hitherto unsuspected by modern writers, is argued from literary and archaeological evidence. Under him Samos reached the peak of her prosperity basing megaloprepeia at home upon increased trade abroad. It was this tyrant who reformed the whole basis of Samian agriculture, fostered industry (notably the cosmetic trade), and embarked on the programme of public works which so thrilled Herodotos. He gained an empire among the coastal towns of Ionia and ruled the islands as far as Delos, enjoying the powerful alliance of Sparta and Lydia. Yet when Kyros conquered Lydia, Polykrates rejoiced; for Phokaia was destroyed, and she was Samos' strongest commercial rival, having seized the monopoly of the Tartessian trade. Polykrates was confident that the shipless Persians would leave him alone. In this he was mistaken, and after a raid in which the Heraion was burned down and a cemetery desecrated, the tyranny fell and was replaced by an oligarchy friendly to Persia c. 540. In 533 Polykrates II made himself tyrant and resumed his father's independent policies. For eight years he enforced a rigid military austerity to equal that of Sparta, and defied the Persians. But by 525 it had become clear that the Persians must in the end conquer, and Polykrates deserted his Egyptian allies, following the Kypriote example in going over to the Persian side. The significance of his famous thalassocracy was that his fleet held the balance between the navies of Egypt and Persian Phoinikia. It was probably this that persuaded the Spartans to attempt to unseat him after his defection. They failed. But in the confusion which followed the death of Kambyses in 522, the local satrap was able to lure Polykrates to his death. Polykrates was succeeded by his servant Maiandrios, who was, however, soon deposed by the new Persian king Dareios, in favour of the old tyrant's brother Syloson. His reign was brief; but his son ruled under the Persians from c. 515 until 499, and again for a year or so after the Ionian Revolt of 499-94. The resources of the insurgents owed not a little to these years of quiet recovery under Aikes. Nevertheless, the Revolt failed, thanks largely to the treacherous behaviour of the Samians at the Battle of Lade in October 495. Samos remained in Persian hands until after the Persian Wars, and sent a contingent to Salamis. In 479 the island was liberated by Leotychidas, and gave valuable help to the Greeks for the Battle of Mykale. The Samians were enthusiastic founder-members of the Delian Confederacy, under a new tyrant Maiandrios II who was killed commanding the national contingent at the Eurymedon in 469. He was replaced by a pro-Athenian democracy, which marked its affection by setting the Athenian olive-branch on the Samian coinage, and by making symbolic gifts of sacred land to Athenian cults; and, more practically, by sending a detachment to join the disastrous Egyptian expedition which failed at Memphis in 454. After the disaster Miletos, Erythrai, and perhaps other Ionian cities, revolted to Persia. In fear of the approach of a Persian fleet to these advanced posts, the Samians urged the Athenians to move the Delian treasury to Athens. It was the last important act of the democratic party; for in this same year they fell before an oligarchic revolution, as is demonstrated by numismatic evidence fully set out in the Supplement. There is no evidence that the Samian oligarchic government took any part in the affairs of the Confederacy of Delos. In 441 yet another boundary dispute broke out between Samos and Priene, as a result of the enrolment of Samos' possession Marathesion among Athens' tributaries, and the consequent loss of the place to the Samian economy. Miletos became involved in warfare with Samos, and appealed to Athens for help. Samos refused Athenian arbitration, and Perikles resolved upon direct intervention. He sailed to Samos and deposed the oligarchs, restoring the democracy. The oligarchs had evidently not expected this action, and were easily routed. But they plotted their return from the security of Anaia, and with Persian help crossed to Samos and regained the government, immediately resuming their war with Miletos. Perikles gathered a greater fleet than before, but even so had to conduct an eight-month siege before the island surrendered. The outcome of the war, Thukydides says, was a matter of considerable uncertainty. But when the end came it was certain enough. By the terms which Perikles imposed Samos lost her fleet, and with it her independence of action. The free history of Samos may be said to end here: henceforward we learn only of the part which Samos played in the history of one or other of the Great Powers.